Analysis of an electromagnetic tube placement device versus a self‐advancing nasal jejunal device for postpyloric feeding tube placement. Issue 1 (29th November 2013) - Boyer, Nathan; McCarthy, Mary S.; Mount, Cristin A.
<x xml:space="preserve">Abstract</x> BACKGROUND Initiation of enteral feeding is an important part of the best practice model for critically ill patients. Although nasogastric feeding is appropriate for the majority of patients requiring short‐term nutrition support, certain patients benefit greatly from postpyloric feeding. OBJECTIVE To determine which of 2 specialized enteral tube systems achieved postpyloric placement on initial insertion attempt most efficiently. DESIGN Retrospective study comparing the Tiger 2 tube (T2T) and Cortrak Enteral Access System (C‐EAS). SETTING Academic medical center, mixed intensive care unit (ICU). PATIENTS All patients admitted to the ICU between 2009 and 2013 who had either a C‐EAS or T2T placed. MEASUREMENTS Success rate for postpyloric placement, congruency of real‐time tube placement with x‐ray confirmation for C‐EAS, and complication rates. RESULTS Seventy‐one T2T and 74 C‐EAS patients were included. The T2T was postpyloric 62% (44/71) of attempted placements. C‐EAS was postpyloric 43% (32/74) of attempted placements (P = 0.03). C‐EAS tracings accurately reflected chest x‐ray findings 83% and 82% for postpyloric and non‐postpyloric insertion, respectively. During the entire study period, no adverse events were recorded. CONCLUSION Our institution evaluated 2 different systems designed to ensure postpyloric placement of a small bore feeding tube. No literature exists directly comparing the 2 systems. Our retrospective review, although limited, showed that the T2T was more effective at postpyloric placement on first attempt. Although 1 benefit of the C‐EAS system may be real‐time visualization, our practice showed this system to be user dependent, which likely led to less success with postpyloric placement. Journal of Hospital Medicine 2014;9:23–28. Published 2013 Society of Hospital Medicine